Self Efficacy and Quality of Life in Chronic Renal Failure Persons on Hemodialysis - Yosi Oktarina; Andika Sulistiawan (Universitas Aisyah Pringsewu, 2022)
Hemodialysis is performed on patients with end-stage renal failure routinely every 2-3 times a week for the patient's survival. However, many physical, psychological, and socio-economic problems impact patients due to routine hemodialysis. It certainly has an impact on the patient's quality of life. Self-efficacy is believed to affect the patient's quality of life. The purpose of this study was to determine the correlation of self-efficacy with the quality of life of chronic renal failure patients undergoing hemodialysis. This research was conducted in the Hemodialysis Room at Raden Mattaher Hospital with a total sample of 62 people. The side technique uses consecutive sampling. The measuring instrument used is SEMCD-6 which assesses self-efficacy and WHOQoL-Bref to assess the patient's quality of life. Data analysis using Spearman correlation. The results of the univariate analysis showed the mean self-efficacy score was (42.47±5.11). The highest mean score was found in the environmental domain (63.77±10.85), and the lowest average was in the physical domain (51.98±7.71). The bivariate analysis found that there was a positive correlation between self-efficacy and quality of life in the four domains (physical, psychological, social relations, and environmental domains) with a p-value less than 0.05 (R = 0.366-0.631). It shows that the better the self-efficacy, the higher the patient's quality of life. It is hoped that nurses can provide motivation and health education to patients and families to increase patient self-efficacy so that the patient's quality of life increases.Abstrak: Hemodialisis dilakukan pada pasien gagal ginjal kronik tahap akhir secara rutin yang dilakukan setiap 2-3 kali dalam seminggu untuk kelangsungan hidup pasien. Namun demikian, sejumlah dampak baik fisik, psikologis, maupun sosial ekonomi dapat timbul pada pasien akibat rutinitas dalam menjalani hemodialisis. Hal ini tentu berdampak pada kualitas hidup pasien. Self efficacy diyakini mempengaruhi kualitas hidup pasien. Tujuan penelitian ini untuk mengetahui korelasi self efficacy dengan kualitas hidup pasien gagal ginjal kronik yang menjalani hemodialisa. Penelitian ini dilakukan di ruang hemodialisa RSUD Raden Mattaher dengan jumlah sampel sebanyak 62 orang. Teknik sampiing menggunakan consecutive sampling. Alat ukur yang digunakan yaitu SEMCD-6 yang digunakan untuk menilai self efficacy dan WHOQoL-Bref untuk menilai kualitas hidup pasien. Analisa data menggunakan korelasi Spearman. Hasil analisis univariat menunjukkan rerata skor self efficacy (42,47±5,11). Skor rerata tertinggi didapatkan pada domain lingkungan (63,77±10,85) dan skor rerata terendah berada pada domain fisik (51,98±7,71). Analisis bivariat ditemukan hasil terdapat korelasi positif self efficacy dengan kualitas hidup pada keempat domain (domain fisik, psikologis, hubungan sosial, dan lingkunga) dengan nilai p-value kurang dari 0,05 (R = 0,366-0,631). Hal ini menunjukkan semakin baik self efficacy, semakin tinggi kualitas hidup pasien. Diharapkan perawat dapat memberikan motivasi dan edukasi kesehatan kepada pasien dan keluarga untuk dapat meningkatkan self efficacy pasien sehingga kualitas hidup pasien meningkat.